Bride wars - Hudson, Kate, 1979-; Riche, Alan, 1926-; Riche, Peter; Yorn, Julie, 1969-; DePaul, Greg.; Wilson, Casey; Raphael, June Diane; Winick, Gary, 1961-; Hathaway, Anne, 1982-; Greenberg, Bryan; Pratt, Chris; Howey, Steve; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2009)
Lifelong best friends Liv and Emma have shared a dream since childhood. Each yearns for the perfect June wedding at the famed Plaza Hotel in New York City. Both find themselves engaged at the same time and go to a wedding coordinator to set up the perfect wedding. A clerical error puts them both down for nuptials on the same day at the same time. One of them will have to switch the date.
English track: Dolby digital 5.1.
Spanish and French tracks: Dolby digital surround
Title from container.
Originally released as a motion picture in 2008.
Special features: 3 deleted scenes including an alternate opening; "The perfect white dress" featurette; theatrical trailers.
Director of photography, Frederick Elmes ; editor, Susan Littenberg ; music, Edward Shearmur.
Keywords: Plaza Hotel (New York, N.Y.) -- Drama; Best friends -- New York (State) -- New York -- Drama; Weddings -- New York (State) -- New York -- Planning -- Drama; Wedding costume -- New York (State) -- New York -- Drama; Marriage service -- New York (State) -- New York -- Drama; Marriage customs and rites -- New York (State) -- New York -- Drama; Romantic comedy films; Video recordings for the hearing impaired; Feature films